Efficacy of Fibroblast Growth Factor Receptor (FGFR) inhibitor Infigratinib on Experimental Autoimmune Encephalomyelitis (EAE), a mouse model of Multiple sclerosis (MS) - Rajendran, Vinothkumar; Justus Liebig University Giessen (My University, 2021)
Multiple sclerosis (MS) is associated with oligodendrocytes damage resulting in demyelination, failure of remyelination and functional loss of neurons. Present therapeutic disease modifying drugs for MS are acting predominantly anti-inflammatory and there is a lack of substances with improving mechanisms of myelin repair. Recent findings in MS patients and its animal models suggested that fibroblast growth factors (FGF) and its receptor (FGFR) signalling plays a role in the pathology of MS and its models. Recent studies on the function of FGFR in MOG35-55-induced experimental autoimmune encephalitis (EAE) showed that deletion of FGFR1 and FGFR2 in oligodendrocytes leads to a less severe disease course, decreased lymphocyte and macrophage infiltration and increased remyelination. Here, we hypothesized that the oral application of a selective FGFR inhibitor infigratinib decreases disease severity and enhance neuronal protection in experimental autoimmune encephalomyelitis. Oral application of infigratinib resulted in a constant decline of disease severity in MOG35-55-induced EAE. The ameliorated disease course was associated with a reduction of cellular inflammation in the CNS, as well as neuroprotective and neuroregenerative effects. The number of mature oligodendrocytes within demyelinating lesions was increased, degeneration of myelin and axons was reduced following application of infigratinib. The limited expression of FGFRs in the spinal cord suggests that infigratinib crosses over the blood-brain barrier and acts in the CNS. Further, infigratinib induces the increased expression of BDNF/TrkB and myelin proteins MBP, PLP, CNPase in spinal cord. The results of this study suggest that short-term administration of infigratinib has the efficiency of ameliorating the severity of EAE by reducing immune cell infiltration and enhancing myelin protein expression.
Keywords: Infigratinib; EAE; FGFR; Multiple Sclerosis; ddc:570